Predicting Tunnel Squeezing: A Discussion based on Two Tunnel Projects - Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2013)
Tunnel squeezing is a phenomenon, which is frequently confronted while tunneling through Himalayan rock mass. Weak and schistose rocks like mudstone, shale, slate, phyllite, schist, highly schistose mica gneiss and the rock mass of the tectonic fault zones are incapable of sustaining high stresses. A reliable and trustworthy prediction on the extent of squeezing is therefore essential. The reliable prediction results help to make strategy regarding stabilizing measures and optimization of tunnel rock support well in advance. This paper is mainly focused in analyzing the tunnel squeezing that took place in connection with the two tunnel cases; i.e. Kali Gandaki ’A’ and Middle Marsyangdi headrace tunnels. The main focus is given to look on the applicability of squeezing analysis using Hoek and Marinos approach in combination with the equation proposed by Panthi for the estimation of rock mass strength for highly schistose rocks of the Himalaya. The measured tunnel convergence (squeezing) and lab tested mechanical properties of the rocks from these two headrace tunnels have been used to verify the applicability of the proposed methods and also the uncertainty analysis approach on squeezing introduced by Panthi. Hydro Nepal; Journal of Water, Energy and Environment Vol. 12, 2013, January Page: 20-25 DOI: http://dx.doi.org/10.3126/hn.v12i0.9027 Uploaded Date : 10/28/2013